Analysis of the Heterogeneity of CD4+CD25+ T Cell TCR β CDR3 Repertoires in Breast Tumor Tissues, Lung Metastatic Tissues, and Spleens from 4T1 Tumor-Bearing BALB/c Mice. (24th September 2020) - Zhang, Teng; Duan, Fangfang; Su, Danhua; Ma, Long; Yang, Jiezuan; Shi, Bin; He, Xiaoyan; Ma, Rui; Sun, Suhong; Yao, Xinsheng
Abstract : To study the homogeneity and heterogeneity of CD4 + CD25 + T cells receptor β -chain complementarity determining region 3 (TCR β CDR3) repertoires in breast tumor tissues, lung metastatic tissues, and spleens from 4T1 tumor-bearing BALB/c mice. We used high-throughput sequencing to analyze the characteristics and changes of CD4 + CD25 + TCR β CDR3 repertoires among tumor tissues, lung metastatic tissues, and spleens. The diversity of the CD4 + CD25 + TCR β CDR3 repertoires in breast tumor tissue was similar to that of lung metastatic tissues and less pronounced than that of spleen tissues. Breast tumor tissues and lung metastatic tissues had a greater number of high-frequency CDR3 sequences and intermediate-frequency CDR3 sequences than those of spleens. The proportion of unique productive CDR3 sequences in breast tumor tissues and lung metastatic tissues was significantly greater than that in the spleens. The diversity and frequency of the CDR3 repertoires remained homogeneous in breast tumors and lung metastatic tissues and showed great heterogeneity in the spleens, which suggested that the breast tissues and lung metastatic tissues have characteristics of CD4 + CD25 + T cells that relate to the tumor microenvironment. However, the number and characteristics of overlapping CDR3 sequences suggested that there were some different CD4 + CD25 + T cells in tumors and in the circulatory immune system. The study may be used to further explore the characteristics of the CDR3 repertoires and determine the source of the CD4 + CD25 + T cells in the breast cancer microenvironment.